Development of Approach to Typology of Internet Communities based on Discursive Markers of Collective Subjectivity - Pavlova, Natalya D; Voronin, Anatoly N; Grebenschikova, Taisiya A; Kubrak, Tina A (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2019)
The article discusses the problems of the typology of network communities, representing the new social reality of modern digital society. The methodology of a comprehensive study of social communities based on socio-psychological and psycholinguistic methods, the use of the discursive approach and the subject category, little studied in relation to large social groups, determine the novelty of the research. According to the main research hypothesis, various forms of group subjectivity, which determine its readiness for joint activities, are manifested in the discourse of the network community, which constitutes it by mediating the interaction of its members, transmitting ideas about the world, values, relations, attitudes and setting patterns of behavior. We deﬁned discursive features of internet communities relevant to the various forms of group subjectivity and subjectivity criteria - interconnectedness, focus on joint activities, etc. A procedure for identifying discursive characteristics of the subjectivity of a network community of various levels (lexical, procedural, semantic) was presented and their examples were given. On this basis, a comparative analysis of network communities, providing for the future creation of their psychological typology was carried out.